The potential of sweet potato (Ipomea batatas (L.) Lamb) as a dual purpose crop in semi-arid crop/livestock systems in Kenya - Karachi, M.K.; Dzowela, B.H. (International Livestock Centre for Africa, 1990)
Investigates production characteristics, forage quality and animal production potential of some selected Kenyan sweet potato accessions for inclusion into crop/livestock production systems. Presents and discusses results of experiments on fibrous root development and tuber development and vine quality. Includes data on chemical composition of vines after 210 days from planting and chemical composition and in vitro dry matter digestibility of rations. Examines the effect of vines and cottnseed cake supplementation on DM intake and calf growth rates.